ANALYSIS OF THE EFFECTIVENESS OF THE GUIDANCE AND COUNSELING PROGRAM IN IMPROVING THE ACHIEVEMENT OF GRADUATE COMPETENCY STANDARDS - Rani, Jania Cahya; Yusuf, Arya; Wulida, Siti Nursipa (TRANSFORMATIONAL LANGUAGE, LITERATURE, AND TECHNOLOGY OVERVIEW IN LEARNING, 2024)
This study investigates how guidance and counseling programs can help schools achieve the Graduate Competency Standards (SKL). Data were collected from 37 high schools and vocational schools in Yogyakarta using descriptive qualitative methods and case studies based on secondary data. Library studies were also used, as well as Simple Random Sampling and Cluster Random Samplin techniques. This article evaluates two main variables: the success of guidance and counseling services and the achievement of SKLs. The purpose of writing this article is to provide an overview of the contribution of guidance and counseling programs to the achievement of SKLs as well as suggestions for improvement. The conclusion is that good guidance and counseling services contribute greatly to the achievement of SKLs because they help students overcome their social, academic, career and personal problems and develop their potential. Educational institutions should continue to improve the quality of these programs to support student success.